LEGAL REGULATION OF PRE-IMPLANTATION GENETIC DIAGNOSTICS: THE INTERNATIONAL EXPERIENCE AND ITS APPLICATION IN THE RUSSIAN FEDERATION IN THE DEVELOPMENT OF THE CONCEPT - Anatolyevna Altynnik, Natalya; Viktorovna Komarova, Valentina; Aleksandrovna Borodina, Mariya; Sergeevich Zenin, Sergey (Revista Inclusiones, 2020)
The relevance of the study of the general principles and patterns of legal regulation of preimplantation genetic diagnostics in foreign countries is determined by the need to develop a concept of legal regulation of this type of diagnostics in Russia. The purpose of this study is to develop the general principles of the concept of legal regulation for pre-implantation genetic diagnostics in Russia. The authors have examined legislative acts, the practice of their application, and the doctrinal sources used in the UK, USA, France, Israel, China, Japan, as well as local regulatory acts of medical organizations. Among the methods used for this study, one can mention general philosophical methods, general and specific scientific methods, special methods (the structural legal method, the comparative legal method, the formal legal method).